ANALISIS POLA HIDUP WBP MENGENAI PERILAKU HIDUP BERSIH DAN SEHAT DI LAPAS - Hendrasta Alief Sukokaryo (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2020)
Awareness about clean and healthy life so that it is not natural to contract the disease should not only focus on the outside community alone or in general. Citizens of Correctional Institutions (WBP) who have committed crimes in prison must also be given guidance and health services, due to the lack of optimal services and positive influences such as examples of directives to maintain clean living behavior. Data in class 1 prisons on June 30, 2019, shows that the number of WBP is 1259 people (WBP), while the capacity is 825 people (WBP). These data indicate the occurrence of excess capacity, which causes many problems such as infectious diseases. This research raises the issue of why itching occurs. This study uses a qualitative method. This study aims to determine the cause of itching infection. The results of this study indicate that itching in prison class 1 Madiun caused by conditions that are less clean water, accompanied by poor block conditions in maintaining cleanliness.